Analysis of Mobiling Innovation Services at Batu City’s Population and Civil Registration Department - Almayda Shalsabella; Diandra Putri Andini; Nur Amalia Hamida (Journal of Transformative Governance and Social Justice, 2025)
According to AS, population administration services are a fundamental aspect of the government system that aims to produce accurate, timely, and quality population documents. Moenir, service itself is the process of fulfilling needs through the direct activities of other people (Moenir, 2005, p. 16). The Population and Civil Registration Service (Dispendukcapil) strategically organizes comprehensive administrative services, from recording births, marriages, and deaths to issuing resident identity cards. The quality of services provided by Dispendukcapil can directly affect public satisfaction and the effectiveness of the government administration system. The success of population administration services is measured through several key indicators, including the level of public satisfaction, the speed of the administrative process, and the accuracy of the information produced. Dispendukcapil has continuously begun to innovate and develop information technology to facilitate public access to various administrative services in this era of sophisticated technology. This study aims to analyze the performance of administrative services in the "mobilizing" innovation owned by Dispendukcapil Batu City, focusing on process speed, transparency, and ease of access for the public. The study will use a descriptive qualitative approach to evaluate various factors influencing service quality, including human resources, technological infrastructure, and applicable administrative procedures. The study results are expected to provide concrete recommendations to optimize a more efficient, responsive, and community-based population administration service system.